Simulação CFD de um sistema de refrigeração para máquinas computacionais portáteis - Valério, Marcos Eduardo Hoffmann (2021)
In this project, a refrigeration system for portable computers, such as notebooks, pocket computers and the like, was developed through the technique known as Computational Fluid Dynamics (CFD). This type of simulation allows predict the behavior of fluids without the need to create a real system. The goal is to develop a system that can keep the computational processor of the Central Processing Unit (CPU) of an open-hardware device at acceptable operating temperatures so that there is no loss of chip performance or physical damage to it. The simulation was developed using free software: the 3D drawing part, carried out in the SALOMÉ program, and the simulation, as well as the visualization of the results, carried out through the set of ANSYS programs. Steady-state and transient analyzes obtained results that enabled the visualization of the simulation variables, as well as the observation of the processor's thermal behavior, molar fraction of the fluids involved, and the efficiency of the heat sinks developed. Furthermore, it was concluded that a purely metal composite heatsink would be the most suitable for the simulated system.